Aplikasi Augmented Reality Geometri Sekolah Dasar Untuk Bangun Datar dan Ruang Menggunakan Metode Marker Based Tracking - Syahrizal Dwi Putra; Diah Aryani; Harlinda Syofyan; Verdi Yasin (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Geometry is an important part of students' mastery of mathematics. In its application, students are still constrained in imagining objects abstractly. It takes the right learning media that is used by teachers and keeps abreast of current technological developments. This study aims to describe flat and spatial geometric objects in teaching geometry using augmented reality learning media based on Android applications so that learning becomes more interesting, concrete and visual equipped with a quiz game feature that contains quizzes that are puzzle games. This application was built using Unity3D and Vuforia SDK and 3D objects created using Blender. This application utilizes the marker method used to determine the point of emergence of 3D objects. The results of application testing using the black box method state that the detection of markers on objects, features and the speed level of devices using the application is running well. The Marker Based Tracking method can be used to recognize flat object markers and spatial planes very well.